Pengaruh Current Ratio, Debt To Equity Ratio Dan Return On Asset Terhadap Harga Saham Perusahaan Perkebunan - Arianti Pratiwi (Universitas Batanghari Jambi, 2019)
Current Ratio, Debt to Equity Ratio and Return On Assets to Stock Prices in Plantation Sector Industrial Companies Listed on the Stock Exchange for the 2013-2017 Period. With an average CR 711.47%, DER 4.90%, ROA 28.52% and the stock price is 28.831.4%.The analytical method used is the classical assumption test (normality test, multicolourarity test, heterokedacity test, autocorrelation test), hypothesis testing (f test, t test), multiple linear analysis, test of the determination coefficient R square. All research data were processed using SPSS version 20.The object in this study is a company listed on the Indonesia Stock Exchange for The period 2013-2017. This study uses financial ratios that can be calculated from annual financial statements. The population received at the Indonesia Stock Exchange is 16 companies. However, not all Plantation Industries listed on the Indonesia Stock Exchange can be sampled in this study. Sampling uses criteria that have been agreed before, after passing the criteria for the number chosen as a sample of 5 companies. Based on predetermined criteria, obtained samples of companies that meet the sample criteria in this study Astra Agro Lestari Tbk, Tunas Baru Lampung Tbk, PP London Sumatera Indonesia Tbk, Sampoerna Agro Tbk, Salim Ivomas Pratam Tbk,Test results F, it is known that the Current Ratio, Debt Ratio to Equity and Asset Returns are considered significant to the Stock Price. While in the t test, there are only two variables, namely CR and ROA variables.The calculated F value is 14,339 with a probability of 0,000 smaller than 0.05 so that it can be concluded that the independent variable (Current Ratio, Debt to Equity Ratio, Return on Assets) together has a significant effect on the stock prices of companies supported on the IDX in 2013 -2017. Changes that occur in stock prices can be done by the variable Current Ratio (CR), Debt Ratio to Equity (DER), Return on Assets (ROA), amounting to 62.5%, the remaining 37.5%, depending on other variables outside the model .